PENGARUH PENAMBAHAN SERAT PELEPAH PISANG PADA PEMBUATAN PAVING BLOCK K-175 - Abdus Salam; Sugeng Dwi Hartantyo (Litbang Pemas - Universitas Islam Lamongan, 2017)
Pavingblock is one of the building material is used asthe top layer of the road structure other than asphalt or concrete. Today, many consumer preferring paving blocks compared to other pavement such as concrete or asphalt. That effort to improve the properties of the less good than paving blocks (eg, less tensile strength and brittle nature) can be done by adding fiber to mixing. One of the natural fiber used are banana midrib fiber, the use of banana midrib fiber as composite materialis a good step to reduce the pile of banana skins were strewn in the garden and also to raise the economic value of banana. The test object to be created is a test object with a mixture of 1: 3 with FAS 0.30 by compaction use manual / conventional, manufacture of each test specimens 3 pieces of normal test specimen without additives followed by paving block with material added together banana midrib fiber from 1% - 5% of the weight of cement used. Results of each - each of specimens have been tested for compressive strength of the test specimen normal to the specimen with additional fiber material as much as 5%. Averages compressive strength calculation results in a sequence of test specimens N, 1%, 2%, 3%, 4% and 5%, ie 224.20 kg / cm2, 192.73 kg / cm2, 119.97 kg / cm2, 98.33 kg / cm2, 78.67 kg / cm2, and 72.77 kg / cm2.